PENGARUH KARAKTERISTIK ANGGARAN TERHADAP HUBUNGAN KEJELASAN DAN SENJANGAN ANGGARAN PADA SEKRETARIAT PROVINSI JAWA TENGAH - Kristensia A. Kayame, 11.05.52.0067; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2016)
This study takes an object at the Regional Secretariat of Central Java province. The problems faced by the Secretariat of Central Java province that the budget-making processes that involve managers across all functions still shows less than optimal, as evidenced by the establishment of budget standards are still not in accordance with the realization that have an impact on the margin is greater with actual costs (inefficiency). The study aims to determine the effect the clarity of the budget targets and budget participation on budgetary slack in the Regional Secretariat of Central Java province. Total sample of 62 respondents. The sampling technique in this study using a stratified proportional random sampling method of sampling where the population has members / elements that are not homogeneous and stratified proportionately. The test results showed that there is a positive and significant influence between the clarity of the budget targets for budgetary slack and other results that there is a positive and significant influence between budget participation on budgetary slack.  Keywords: Budget Goal Clarity, Budget Participation On Budgetary Slack